Effectiveness of Pressurized Metered Dose Inhaler (pMDI) Versus Dry Powder Inhaler (DPI) in Delivering Inhaled Corticosteroid and Long Acting Beta Agonist Among Patients with Uncontrolled Asthma in a Tertiary Care Hospital - Xunaira Qamar; Muhammad Hussain; Salman Ayyaz; Sarwat Saif; Shahmeer Anjum; Laiba Qamar Butt (Pakistan Journal of Health Sciences, 2026)
Uncontrolled asthma remains common in Pakistan despite regular use of inhaled corticosteroid and long-acting beta-agonist combination therapy. Drug delivery may differ according to the inhaler device. Pressurized metered-dose inhalers (pMDIs) and dry powder inhalers (DPIs) are the most frequently prescribed devices, but local comparative evidence remains limited. Objective: To compare the short-term effectiveness of pMDI and DPI in delivering inhaled corticosteroid and long-acting beta-agonist therapy among adults with uncontrolled asthma in a tertiary care hospital. Methods: This parallel randomized controlled trial was conducted at the Department of Pulmonology, Services Institute of Medical Sciences, Lahore. A total of 146 adults with uncontrolled asthma were randomized equally to pMDI (n=73) or DPI (n=73). The primary outcome was the proportion of participants achieving at least a 0.5-point reduction in Asthma Control Questionnaire (ACQ) score at 8 weeks. Secondary outcomes included mean ACQ change, change in forced expiratory volume in one second (FEV₁ % predicted), exacerbations, inhaler technique score, and adverse events. Results: Baseline age, sex, body mass index, asthma duration, baseline FEV₁ % predicted, and ACQ score were comparable between groups. Greater mean ACQ improvement was observed in the pMDI group than in the DPI group (4.6 ± 3.1 vs 3.2 ± 2.9; p = 0.006). FEV₁ improvement was also greater with pMDI (p=0.021). Exacerbations occurred in 24.7% of pMDI users and 39.7% of DPI users (p=0.048). Adverse events were mild and similar between groups. Conclusion: pMDI use was associated with better short-term asthma control and fewer exacerbations; larger multicentre studies are needed.